POSTOPERATIVE DELIRIUM: MODERN ASPECTS OF DIAGNOSIS, PREVENTION AND THERAPY - M. M. Sokolova; M. Y. Kirov; K. V. Shelygin (Кубанский научный медицинский вестник, 2018)
Delirium is an acute change in mental status in the form of disorientation in time and space, loss of attention and disruption of sleep/wake patterns. From the psychopathological point of view, delirium is a qualitative disorder of consciousness with concomitant disorders of perception (illusions and hallucinations). Postoperative delirium (POD) is one of the postoperative complications that occur in patients of any age, including children. As a rule, POD develops within 5-7 days after the surgery. The frequency of its occurrence varies in different age groups. Nowadays more than 230 million surgeries are performed annually in the world, and the frequency of POD depends on the type of surgical operations, age of a patient and a number of risk factors. The effects of POD include cognitive disorders, prolonged hospitalization, increased mortality, leading to a significant increase in healthcare costs. The implementation of the protocol on the diagnosis and therapy of delirium, based on modern recommendations, can improve the clinical outcome.